Diplomatic protocol in the empire of Amir Temur (based on the works of Rui Gonzalez de Clavijo) - S. M. Ulzhaeva; D. S. Kidirniyazov (Nomadic Civilization: Historical Research)
The article examines the diplomatic protocol used in the courtyard of Sohibkiran Amir Temur. It was during the reign of this legendary eastern ruler that the foundations of the diplomatic protocol were developed, which contributed to strengthening the respect and trust of foreign envoys to the Turanian state and its ruler, turning the country into one of the most powerful states in the East. This diplomatic ceremony is analyzed in the article on the example of the visit of the Ambassador of the King of Spain Rui Gonzalez de Clavijo to Samarkand in 1403-1406 and on the basis of his memoirs written during this mission and following it. Many norms and rules for organizing the visit of foreign envoys to Turania, which operated in the courtyard of Amir Temur, were indirectly included in the modern diplomatic protocol and today serve the extremely important cause of the development of political and business cooperation between countries, peoples, as well as international interacting organizations representing both social and political sphere, and business circles.